Penyetaraan Gender di Sri Lanka - Bayu Setyawan (Department of Political Science - Universitas Sains Al-Qur’an, 2019)
The issue of gender inequality in Sri Lanka has made women get discriminatory treatment in various ways, both in the social and political manner, as well as in education and employment. UNDP has made efforts to fight for the rights of Sri Lankan women. However, these efforts impressed without significant development. This study tries to explain the various obstacles faced by UNDP. The study uses the concept of an international regime with qualitative analysis methods. The results of the study indicate that UNDP has not succeeded in equalizing gender in Sri Lanka because the separatist Tigers conflict has hampered international assistance.